Collapse and Fire Hazards at the Construction Sites and their Economic Impact on the Nation? - Sayah, Elias B.; Ranadive, Dr. M. S. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The Saudi Economy is losing annually Millions of Saudi Currency and that due to ignorance ofthe safety requirements.Abdullah Mubarak: capital is a coward and accidents are closely linked to the investmentmovement in the country.Muhammad Abdullah: some construction companies ignore safety requirements with to savemoney Engineer Ahmad Ghali: A tough control should be done to construction works. Someentrepreneurs have no idea about the conditions of security and safety.Magdy Tawfiq engineer: Safety requirements must be compulsorily applied to all establishmentsand construction companies and an information centre about all companies, accidents andconstruction sites  Fawzi Al-buheiri Advisor: current laws are sufficient to deter offenders and required to beactivated firmly  Attainment Written by: Ahmed Abdullatif achieved: providing security andsafety for commercial and industrial installations of the most important challenges facing thenational economy as not only a victim of accidents and fires which result in heavy material losses,but to the security and safety relationship to attract new investment and create a safe climate forinvestment...These challenges, which began with the construction boom and the business for years and wasone of the most important manifestations of major expansions in construction projects that requirenecessarily implemented strong security fence and safety.Since the beginning of the year 2003 started increasing incidents of collapses and fires strikinglyat the same time, concern over the ability of the national economy in a balance between the desireto grow and expand and provide protection to the cowardly capital in nature and always seekerareasBefore this challenge, there was a formal recognition of the seriousness of the phenomenon on thenational economy in the new legislation and decisions that will activate the role of the safetydevices in economic activities through civil defense and municipal organizations. .Perhaps the most notable official efforts in this domain awareness events advisory offices andconstruction companies in the new rules for security and safety after the adoption of the new USAcode.